2016
DOI: 10.2147/dddt.s123318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral absorption models for pregabalin: usefulness of transit compartment model

Abstract: Pregabalin is an anticonvulsant used for the treatment of neuropathic pain and partial seizure in adults. The aim of this study was to develop a population pharmacokinetic (PK) model to describe the absorption characteristics of pregabalin given fasted or after meals. Data from five healthy subject PK studies (n=88) of single- or multiple-dose pregabalin (150 mg) were used. Pregabalin was administered twice daily, without meals or 30 min after a meal (regular or high-fat diet) in the morning and 30 min or 4 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
2
6
1
Order By: Relevance
“…Our developed structural PK model corresponds with previously published models in terms of model structure and rapid absorption of pregabalin after a lag time . The research performed by Hong et al . investigated different structural oral absorption models for pregabalin in which they reported that a first‐order absorption process did not suffice.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our developed structural PK model corresponds with previously published models in terms of model structure and rapid absorption of pregabalin after a lag time . The research performed by Hong et al . investigated different structural oral absorption models for pregabalin in which they reported that a first‐order absorption process did not suffice.…”
Section: Discussionsupporting
confidence: 64%
“…Additional sampling in the absorption phase, between 0 and 1 hour after dosing, could improve the characterization of the absorption phase of pregabalin, which would allow for a better comparison with previous analyses. The use of GFR in healthy subjects as a covariate on CL was also suggested by Hong et al 27 However, this could not be confirmed in this study, which may be explained by our inclusion of the allometric relationship of weight on CL, as there is multicollinearity between body weight and the Cockroft-Gault derived GFR, or the low sample size used in this study. The inclusion of allometric scaling on the V d and CL of pregabalin gave a significant drop in OFV.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Pregabalin’s bioavailability is over 90% and is dose independent [ 37 ]. Food does not affect pregabalin’s overall exposure; however, it can reduce the rate of absorption with the content of the food having little effect on this [ 38 , 39 ]. Maximal serum concentrations appear 0.7–1.3 h post-dose [ 39 ] with the serum half-life ranging from 4.6 to 6.8 h [ 39 ].…”
Section: Methodsmentioning
confidence: 99%